Perilaku Merokok dalam Pandangan Islam - Nadira Tatya Adiba; Arsanti, Meilan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2023)
Smoking is a very common behavior or habit in Indonesia. However, in the long term, this behavior is very dangerous for health because the content in cigarettes can cause various health problems. In this decade, there has been a significant increase in the number of adult smokers by 8.8 million people, from 60.3 million in 2011 to 69.1 million smokers in 2021, as recorded in the Global Adult Tobacco Survey (GATS). Even though many people are aware of the dangers of smoking, cigarette enthusiasts, especially in Indonesia, are increasing every year. The problem regarding the increasing number of cigarette users never stops and always raises pros and cons it. A review of Islamic law regarding smoking can also be a factor in the amount of cigarette consumption. At present, the management of the Indonesian Ulema Council (MUI) forbids smoking on the basis that the consequences of smoking are more than the benefits provided by smoking; however, several other scholars have a different view of making smoking illegal because these scholars have found no evidence that prohibits smoking. cigarette. Objective: To determine the effect of the pandemic and Islamic law on smoking behavior.